Armenian massacres or the sword of Mohammed : containing a complete and thrilling account of the terrible atrocities and wholesale murders committed in Armenia by Mohammedan fanatics : including a full account of the Turkish people, their history, government manners, customs and strange religious belief. - Greene, Frederick Davis. (Philadelphia)
1 CD-ROM.